(untitled) (Asian Journal of Pharmaceutics (AJP), 2025)
Aim: The objective of this research work was to analyze the effect of experimental components (homogenization time, speed of homogenization, and time of sonication) on the characterization of cubosomes loaded with Lidocaine Hydrochloride (LH). Materials and Methods: The Top-down method was adopted to prepare LH cubosomes using lipid (Glyceryl Monooleate), stabilizer (Poloxamer-407) along with water in varied proportions. 32 factorial design was adopted to explain how the two independent factors, that is, homogenization speed and sonication time affect the four responses at varied levels of the processing parameters for the preparation of drug-encapsulated cubosomes. Results and Discussion: The most acceptable entrapment capacity was found at a homogenization speed of 50 rpm and sonication time employed for 10 min for the formulation LT8 within the confidence intervals adopted by the 32 factorial design. LT8 was found to have Entrapment efficiency (EE) of 75 percent, Zeta potential of 21.5 mV, vesicle size of 150.3± 0.77 nm, and PolyDispersibility Index of 0.278. As Hominization speed increased there was a noticeable improvement in the characterization of cubosomes, however, enhanced characterization parameters were observed in dispersions prepared with a medium level of sonication time. Conclusion: A steady dispersion of LH was formed with a high level of speed of homogenization and a medium level of sonication time to attain the desired parameters for the characterization of cubosomes. Therefore, it is concluded that the speed of homogenization of 50 rpm and sonication time of 10 min resulted in a stable dispersion.